(untitled) (Cold Spring Harbor, N.Y., 2003)
DNA microarray technology is a new and powerful means to analyze genomes and characterize patterns of gene expression. Its applications are widespread across the many fields of plant and animal biological and biomedical research. This manual, designed to extend and to complement the information in the best-selling Molecular Cloning, is a synthesis of the expertise and experience of more than 30 contributors-all innovators in a fast-moving field. DNA Microarrays provides authoritative, detailed instruction on the design, construction, and applications of microarrays, as well as comprehensive descriptions of the software tools and strategies required for analysis of images and data.
Keywords: DNA microarrays,Vi mạng ADN; Laboratory manuals,Sổ tay phòng thí nghiệm